Sind Staukosten externe Kosten? Versuch einer terminologischen Flurbereinigung. - Cerwenka, Peter; Meyer-Rühle, Olaf (Deutscher Verkehrs-Verl., 2008)
Das Straßeninfrastrukturangebot hält nicht Schritt mit der wachsenden Straßenverkehrsnachfrage. Verkehrsstaus werden häufiger, und damit steigen die volkswirtschaftlichen Kosten, die aus Staus resultieren. Welche Kosten sind dies im Einzelnen, und für welche Teile kommen die Verursacher bereits auf? Wie sind die verbleibenden, externen Kosten im Rahmen einer Transportkostenrechnung für die Straße unter Ausschluss von Doppelzählungen zu behandeln? Die Autoren melden methodische Bedenken gegen die von der Europäischen Kommission propagierte Vollanlastung von Staukosten als externen Kosten an. Sie erklären dies am Beispiel der schweizerischen Transportrechnung für schwere Lkw.

The European Commission treats congestion costs as a separate transport cost component. The authors explain that congestion costs are the sum of congestion impacts on four of the five basic transport cost categories: time of transported passengers and goods; vehicle operations; accidents; and (noise, pollutants and CO2) emissions (but not infrastructure usage). All environmental costs and a part of accident costs (as long as not internalised by insurance payments or payments of the driver/owner) are external costs. Internalisation of infrastructure and external costs is on the agenda of national and EU transport policies. Simulations suggest that in Switzerland the full recovery of external and infrastructure costs of heavy goods vehicles has already been achieved in 2005 through the present charging system. To justify increased rates effective since January 1st 2008, the Swiss government claims that congestion costs are external costs. The authors argue that congestion costs are either internal costs (transport time and vehicle operations) or are already to a large extent included in the relevant external cost components when appropriate charge levels are calculated.
Are congestion costs external costs?
Keywords: Verkehr; Straßenverkehr; Lastkraftwagenverkehr; Verkehrsinfrastruktur; Transportkosten; Kostenrechnung; Straßengüterverkehr; Verkehrssystem; Verkehrsplanung; Staukosten; Externe Kosten; Schwerverkehr; Maut